Civil Law Consequences of War іn the Context of Compensation for Damage to Individuals and Legal Entities - Valendiuk, Oleh (Problems of legality, 2025)
The relevance of the study is stipulated by the further increase in the number of cases of damage to individuals and legal entities as a result of prolonged armed aggression, which necessitates a comprehensive analysis of the civil law mechanisms for its compensation. In the current conditions of war, there is an urgent need for effective instruments of legal protection of affected entities, as well as for the development of law enforcement practice for the restoration of violated property rights of both individuals and legal entities. The purpose of the study is to identify and investigate the civil law consequences of the damage caused by the war, and to analyse the means and procedures that can be used to compensate for it. The study applies a number of scientific methods: a systematic approach (to analyse the relationship between national and international law in the field of compensation for damage), a comparative legal method (to assess the practice of other states in similar conflicts), a formal legal method (to analyse regulations and court decisions), methods of analysis and synthesis (to identify key trends and formulate generalisations). The study outlines the main types of damage to be compensated, as well as the forms of civil liability that may be applied to the perpetrators of damage. The author reviews current Ukrainian legislation, court practice and the State’s international obligations in the sphere of protection of victims’ rights. The author identifies the problems associated with the exercise of the right to compensation, particularly the difficulty of identifying specific perpetrators, procedural barriers and lack of sufficient financial resources. Prospects for further research include the development of effective mechanisms for compensation, integration of international experience and improvement of the legal framework in order to ensure real access to justice for victims